TNF‐α‐mediated reduction in PGC‐1α may impair skeletal muscle function after cigarette smoke exposure - Kechun Tang; Peter D. Wagner; Ellen C. Breen (2009)
Abstract Skeletal muscle dysfunction contributes to exercise limitation in COPD. In this study cigarette smoke exposure was hypothesized to increase expression of the inflammatory cytokine, TNF‐α, thereby suppressing PGC‐1α, and hence affecting down stream molecules that regulate oxygen transport and muscle function. Furthermore, we hypothesized that highly vascularized oxidative skeletal muscle would be more susceptible to cigarette smoke than less well‐vascularized glycolytic muscle. To test these hypotheses, mice were exposed to cigarette smoke daily for 8 or 16 weeks, resulting in 157% (8 weeks) and 174% (16 weeks) increases in serum TNF‐α. Separately, TNF‐α administered to C2C12 myoblasts was found to dose‐dependently reduce PGC‐1α mRNA. In the smoke‐exposed mice, PGC‐1α mRNA was decreased, by 48% in soleus and 23% in EDL. The vascular PGC‐1α target molecule, VEGF, was also down‐regulated, but only in the soleus, which exhibited capillary regression and an oxidative to glycolytic fiber type transition. The apoptosis PGC‐1α target genes, atrogin‐1 and MuRF1, were up‐regulated, and to a greater extent in the soleus than EDL. Citrate synthase (soleus—19%, EDL—17%) and β‐hydroxyacyl CoA dehydrogenase (β‐HAD) (soleus—22%, EDL—19%) decreased similarly in both muscle types. There was loss of body and gastrocnemius complex mass, with rapid soleus but not EDL fatigue and diminished exercise endurance. These data suggest that in response to smoke exposure, TNF‐α‐mediated down‐regulation of PGC‐1α may be a key step leading to vascular and myocyte dysfunction, effects that are more evident in oxidative than glycolytic skeletal muscles. J. Cell. Physiol. 222: 320–327, 2010. © 2009 Wiley‐Liss, Inc.